Application of Mulberry (Morus alba L.) for Supplementing Antioxidant Activity in Extruded Thai Rice Snack - Chulaluck Charunuch; Plernchai Tangkanakul; Saowaluk Rungchang; Vayooh Sonted (Agriculture and Natural Resources, 2008)
Owing to creation of Thai rice snack with health benefits for higher potential in commercial scale, mulberry leaf was applied in the production of extruded snack product. Mulberry leaf in dried powder form was mixed with rice, corn, soy, sugar, oil, vitamins and minerals to investigate the operating conditions with twin-screw extruder at varying mulberry powder content (5, 7.5 and 10%), screw speed (300 and 350 rpm) and feed moisture (13, 15 and 17%) in the 3 × 2 × 3 factorial experiment. The extrudates were examined of functional properties (antioxidant activity and phenolic compounds) and some physical characteristics (expansion ratio, bulk density, texture measurement and organoleptic test). The results had shown that at higher mulberry content (10%), the product was difficult to operate, unsmooth shape and less expand. While lower screw speed (300 rpm) and moderate moisture content (15%) gave suitable expansion and bulk density with better preference in appearance. This product still has antioxidant activity and phenolic compounds which corresponded to the optimum operating condition (5% mulberry content, 300 rpm and 15% feed moisture) from the statistical analysis. Finally, the finished product was evaluated in the pattern of nutrition labeling, microbiological test and packed in metallize bag to examine for moisture content, aw, colour, TBA number, antioxidant activity and sensory test during storage time (0-4 months) at room temperature.